Characteristic of Edelweiss Park Agrotourism Visitorsm in the Covid-19 Pandemic Time - I Gede Bagus Dera Setiawan; Ni Made Classia Sukendar; Gede Mekse Korri Arisena (UNIVERSITAS SEMBILANBELAS NOVEMBER KOLAKA, 2022)
Tourists have a vital role in the sustainability of a tourist destination. Edelweiss Park Agrotourism is a nature-based tourist destination managed by the local community, or Community Based Tourism (CBT). During the Covid - 19 pandemic still received visits from tourists. Researchers tried to examine from which areas tourists came to visit Edelweis Park Agrotourism during a pandemic using descriptive qualitative and quantitative analysis with a total sample of 100 which was determined using the accidental sampling method.From the discussion, it can be concluded that the characteristics of visitors based on the area of origin are divided into two, the first, are tourists who come from Bali spread from Denpasar, Bangli, Karangasem, Gianyar, Tabanan, Badung, and Klungkung. While from outside Bali, they are distributed from the areas of Lombok, Banyuwangi, West Java, East Nusa Tenggara (Kupang, Sumba, Flores), Surabaya, Jakarta, Tangerang, and West Kalimantan; The characteristics of visitors based on gender were dominated by female visitors as much as 64%; The characteristics of visitors based on average age are dominated by those aged 18 to 24 years with a total of 49 people (49%). Characteristics of visitors based on occupation, dominated by visitors who work as private employees as many as 53 people (53%); The characteristics of visitors based on the frequency of visits are dominated by first-time visitors (84%); Visitor characteristics based on information sources are dominated by information obtained from social media (71%).